On the implementation and consequences of the oceanic currents feedback in ocean–atmosphere coupled models. (September 2019) - Renault, L.; Lemarié, F.; Arsouze, T.
Abstract: The Current FeedBack (CFB) to the atmosphere simply represents the influence of the surface oceanic currents on near-surface wind and surface stress. As the CFB has a significant influence on the oceanic circulation, it is crucial to implement it properly in a coupled ocean–atmosphere model. In this study, we first detail the modifications to be implemented into atmospheric models to account for the CFB. In the computation of air–sea fluxes, the relative winds, i.e., the difference between the near-surface winds and the surface oceanic currents, instead of absolute winds have to be used (Modification M1). However, because of the implicit treatment of the bottom boundary condition in most atmospheric models, the use of relative winds also involves a modification of the tridiagonal problem associated with the discretization of the vertical turbulent viscosity (Modification M2). Secondly, we show both analytically and using global coupled simulations that omitting M2 leads to a large underestimation of the surface stress curl response to the CFB and, subsequently, of the coupling coefficient between mesoscale surface stress curl and surface current vorticity. As a consequence, the dampening of the mesoscale activity induced by the CFB is strongly reduced (by a minimum a factor of 2 or more). The practical implementation of the CFB must be done carefully in the atmospheric component of a coupled model in order to avoid a large underestimation of the CFB effect on the oceanic circulation. Highlights: In coupled models the Current Feedback affects both the wind-stress norm and orientation. Modification of the bulk formulation insures to consider the effect on the stress norm. Modification of the discretization of turbulent vertical mixing term is also needed. The latter is necessary to properly compute the wind-stress orientation. By omitting it, the dampening of the oceanic mesoscale activity is underestimated.